2010
DOI: 10.1161/circulationaha.110.948562
|View full text |Cite
|
Sign up to set email alerts
|

OMEGA, a Randomized, Placebo-Controlled Trial to Test the Effect of Highly Purified Omega-3 Fatty Acids on Top of Modern Guideline-Adjusted Therapy After Myocardial Infarction

Abstract: MD; for the OMEGA Study GroupBackground-There is no randomized, double-blind trial testing the prognostic effect of highly purified omega-3 fatty acids in addition to current guideline-adjusted treatment of acute myocardial infarction. Methods and Results-OMEGA is a randomized, placebo-controlled, double-blind, multicenter trial testing the effects of omega-3-acid ethyl esters-90 (1 g/d for 1 year) on the rate of sudden cardiac death in survivors of acute myocardial infarction, if given in addition to current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
358
3
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(404 citation statements)
references
References 27 publications
6
358
3
15
Order By: Relevance
“…1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 Part of the reason may involve differences between the classes of drugs studied, such as fibrates, niacin, and omega‐3 fatty acids. Even among omega‐3 fatty acid studies, there are marked differences with respect to the relatively low doses of omega‐3 administered and the ratio of EPA to DHA 16, 17, 18, 19, 20, 21, 22, 23, 24. In addition, different TG‐lowering therapies may exert differential effects across lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 Part of the reason may involve differences between the classes of drugs studied, such as fibrates, niacin, and omega‐3 fatty acids. Even among omega‐3 fatty acid studies, there are marked differences with respect to the relatively low doses of omega‐3 administered and the ratio of EPA to DHA 16, 17, 18, 19, 20, 21, 22, 23, 24. In addition, different TG‐lowering therapies may exert differential effects across lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were performed in single countries prior to current treatment guidelines, and therefore provide supportive but not conclusive evidence of CV benefit. Other more recent omega‐3 therapy outcome studies conducted in the presence of statins have been less encouraging, but these studies were characterized by evaluating nonhypertriglyceridemic patient populations (eg, TG <200 mg/dL) and administering low doses of long‐chain omega‐3 fatty acids (eg, eicosapentaenoic acid [EPA] and/or docosoahexaenoic acid [DHA]) 19, 20, 21, 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…The results of those studies were not confirmed by later works, including the OMEGA study, in which no benefits attributable to omega-3 acids supplementation were noted [14]. Therefore, it is necessary to conduct further studies in order to clarify these discrepancies, determine the factors affecting the efficacy of supplementation, and fully explain the mechanisms of potentially beneficial activity of omega-3 acids.…”
Section: Introductionmentioning
confidence: 85%
“…Some of the more recent trials such as the OMEGA trial [34] and the Alpha Omega Trial [35] have also shown some conflicting results. The OMEGA trial [34] is a randomized controlled multi-center trial which enrolled 3851 patients and compared patients receiving 1 g/d of omega-3 fatty acids versus placebo for one year and was unable to show a significant difference in CV outcomes in post -MI patients.…”
Section: Evidence In CV Diseasementioning
confidence: 99%
“…The OMEGA trial [34] is a randomized controlled multi-center trial which enrolled 3851 patients and compared patients receiving 1 g/d of omega-3 fatty acids versus placebo for one year and was unable to show a significant difference in CV outcomes in post -MI patients. This discrepancy could have potentially been from the improvements in medical therapy and stent technology from the decade older trials, thus resulting in a lower number of events in the placebo-treated patients.…”
Section: Evidence In CV Diseasementioning
confidence: 99%